Ethnic enclaves and ethnoburbs: are there differences in associations with juvenile offense type among Asian Americans?. Issue 1 (2nd January 2023) - Tam, Christina C.
ABSTRACT: Little is known about the neighborhood context of offending for Asian American youth. The current study differentiates between coethnic neighborhood types and considers if residence in ethnoburbs –a more recently conceptualized coethnic neighborhood–is associated with more serious arrests (for substance, property, weapon, or violent offenses). Asian youth in ethnic enclaves had lower odds of a violence arrest relative to youth in non-coethnic neighborhoods. Youth in ethnoburbs had higher odds of a weapons arrest, but this association is attenuated after adjusting for individual-level covariates. Implications for future research include exploring mechanisms for place-based targeted intervention strategies.